Synthesis and antimicrobial study of N-[4-(2-piperidine-1-yl-ethoxy) phenyl] acetamide analogues - H. P. Jayadevappa, G. Nagendrappa, S. Umesha, S. Chandrashekar (Journal of Applied Pharmaceutical Science)
In the present study, a novel series of N-[4-(2-piperidine-1-yl-ethoxy) phenyl]-acetamides were synthesized from 4-aminophenol and characterised by IR, 1H-NMR, Mass spectral studies and elemental analysis. The antimicrobial potency of compounds is tested against variety of fungal and bacterial strains by disc agar diffusion technique. in comparison to to fluconazole and chloramphenicol respectively. Some of the synthesized compounds exhibit the potency comparable to that of standard drugs.
Keywords: N-[4-(2-piperidine-1-yl-ethoxy)phenyl]-acetamide, Sy